Pregunta
upstudy study bank question image url

1. Find amplitude of \( \frac{3+2 i}{3-2 i} \) \( \frac{3+2 i}{3-2 i} \) का कोणांक ज्ञात कीजिए। 2. Show that \( \mathrm{f}(\mathrm{z})=\bar{z} \) is not differentiable at any point. सिद्ध कीजिए कि \( \mathrm{f}(\mathrm{z})=\bar{z} \) कसी भी बिन्दु पर अवकलनीय नहीं है। 3. Show that \( \mathrm{u}=\mathrm{x}^{3}-3 \mathrm{xy}^{2} \) is a harmonic function. 4. सिद्ध कीजिए \( \mathrm{u}=\mathrm{x}^{3}-3 \mathrm{xy}^{2} \) एक प्रंसवादी फलन है। Find the radius of convergence of the power series.

Ask by Watkins Norris. in India
Jan 23,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

1. The amplitude of \( \frac{3+2i}{3-2i} \) is \( \tan^{-1}\left(\frac{12}{5}\right) \). 2. The function \( f(z) = \bar{z} \) is not differentiable at any point. 3. The function \( u = x^3 - 3xy^2 \) is a harmonic function. 4. The function \( u = x^3 - 3xy^2 \) is analytic with \( v = 3xy^2 - y^3 + C \). 5. The radius of convergence of the power series depends on the specific series; additional information is needed to determine it.

Solución

Let's solve each part of your problem step by step. ### 1. Find the amplitude of \( \frac{3+2 i}{3-2 i} \) To find the amplitude (or argument) of the complex number \( \frac{3+2 i}{3-2 i} \), we can first simplify it. **Step 1: Simplify the expression.** Multiply the numerator and denominator by the conjugate of the denominator: \[ \frac{3+2i}{3-2i} \cdot \frac{3+2i}{3+2i} = \frac{(3+2i)(3+2i)}{(3-2i)(3+2i)} \] **Step 2: Calculate the denominator.** \[ (3-2i)(3+2i) = 3^2 - (2i)^2 = 9 - (-4) = 9 + 4 = 13 \] **Step 3: Calculate the numerator.** \[ (3+2i)(3+2i) = 3^2 + 2 \cdot 3 \cdot 2i + (2i)^2 = 9 + 12i - 4 = 5 + 12i \] **Step 4: Combine results.** Now we have: \[ \frac{3+2i}{3-2i} = \frac{5 + 12i}{13} = \frac{5}{13} + \frac{12}{13}i \] **Step 5: Find the amplitude.** The amplitude (or argument) \( \theta \) can be found using: \[ \theta = \tan^{-1}\left(\frac{\text{Imaginary part}}{\text{Real part}}\right) = \tan^{-1}\left(\frac{12/13}{5/13}\right) = \tan^{-1}\left(\frac{12}{5}\right) \] Now, let's calculate this value. ### 2. Show that \( f(z) = \bar{z} \) is not differentiable at any point. To show that \( f(z) = \bar{z} \) is not differentiable, we can use the Cauchy-Riemann equations. **Step 1: Express \( z \) in terms of \( x \) and \( y \).** Let \( z = x + iy \), then \( \bar{z} = x - iy \). **Step 2: Identify \( u \) and \( v \).** Here, \( u(x, y) = x \) and \( v(x, y) = -y \). **Step 3: Calculate partial derivatives.** \[ \frac{\partial u}{\partial x} = 1, \quad \frac{\partial u}{\partial y} = 0, \quad \frac{\partial v}{\partial x} = 0, \quad \frac{\partial v}{\partial y} = -1 \] **Step 4: Check Cauchy-Riemann equations.** The Cauchy-Riemann equations state that: \[ \frac{\partial u}{\partial x} = \frac{\partial v}{\partial y} \quad \text{and} \quad \frac{\partial u}{\partial y} = -\frac{\partial v}{\partial x} \] Substituting the values: 1. \( 1 \neq -1 \) (not satisfied) 2. \( 0 \neq 0 \) (satisfied) Since the first equation is not satisfied, \( f(z) = \bar{z} \) is not differentiable at any point. ### 3. Show that \( u = x^3 - 3xy^2 \) is a harmonic function. A function \( u(x, y) \) is harmonic if it satisfies Laplace's equation: \[ \frac{\partial^2 u}{\partial x^2} + \frac{\partial^2 u}{\partial y^2} = 0 \] **Step 1: Calculate the first derivatives.** \[ \frac{\partial u}{\partial x} = 3x^2 - 3y^2 \] \[ \frac{\partial u}{\partial y} = -6xy \] **Step 2: Calculate the second derivatives.** \[ \frac{\partial^2 u}{\partial x^2} = 6x \] \[ \frac{\partial^2 u}{\partial y^2} = -6x \] **Step 3: Check Laplace's equation.** \[ \frac{\partial^2 u}{\partial x^2} + \frac{\partial^2 u}{\partial y^2} = 6x - 6x = 0 \] Since Laplace's equation is satisfied, \( u \) is a harmonic function. ### 4. Show that \( u = x^3 - 3xy^2 \) is an analytic function. To show that \( u \) is analytic, we need to find a corresponding \( v \) such that \( f(z) = u + iv \) is differentiable. **Step 1: Find \( v \) using the Cauchy-Riemann equations.** From the previous part, we have: \[ \frac{\partial u}{\partial x} = 3x^2 - 3y^2, \quad \frac{\partial u}{\partial y} = -6xy \] Using Cauchy-Riemann equations: 1. \( \frac{\partial v}{\partial x} = -\frac{\partial u}{\partial y} = 6xy \) 2. \( \frac{\partial v}{\partial y} = \frac{\partial u}{\partial x} = 3x^2 - 3y^2 \) **Step 2: Integrate to find \( v \).** Integrating \( \frac{\partial v}{\partial x} \): \[ v = 3xy^2 + g(y) \] Now differentiate with respect to \( y \): \[ \frac{\partial v}{\partial y} = 6xy + g'(y) \] Setting this equal to \( 3x^2 - 3y^2 \): \[ 6xy + g'(y) = 3x^2 - 3y^2 \] This implies \( g'(y) = -3y^2 \), so integrating gives: \[ g(y) = -y^3 + C \] Thus, \( v = 3xy^2 - y^3 + C \). ### Radius of Convergence of the Power Series To find the radius of convergence of a power series, we typically use the formula: \[ R = \frac{1}{\limsup_{n \to \infty} |a

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Bonus Knowledge

आपके पहले प्रश्न का उत्तर देते हुए, \( \frac{3+2i}{3-2i} \) का संकुचन (amplitude) ज्ञात करने के लिए, सबसे पहले इसे कार्टेशियन रूप में परिवर्तित करें। इसे आप गुणा करके सरल कर सकते हैं: \[ \frac{(3+2i)(3+2i)}{(3-2i)(3+2i)} = \frac{3^2 + 2\cdot3\cdot2i - 4}{3^2 + 4} = \frac{5 + 12i}{13} \] इसका संकुचन \( \sqrt{5^2 + 12^2} = \sqrt{169} = 13 \) होगा। अब, कोणांक ज्ञात करने के लिए \( \tan^{-1} \left( \frac{\text{Im}}{\text{Re}} \right) = \tan^{-1} \left( \frac{12}{5} \right) \) का उपयोग करें। दूसरे प्रश्न के लिए, \( f(z) = \bar{z} \) की अवकलनीयता सिद्ध करने के लिए, हमें दिखाना होगा कि Cauchy-Riemann समीकरण संतुष्ट नहीं होते हैं। \( z = x + iy \) के लिए, \( f(z) = x - iy \) को देखिए। यहाँ \( u = x \) और \( v = -y \) हैं। Cauchy-Riemann समीकरण के अनुसार: \[ \frac{\partial u}{\partial x} = 1, \quad \frac{\partial v}{\partial y} = -1 \] और \[ \frac{\partial u}{\partial y} = 0, \quad \frac{\partial v}{\partial x} = 0 \] चूंकि समीकरण संतुष्ट नहीं होते, अतः \( f(z) \) किसी भी बिंदु पर अवकलनीय नहीं है। अगले प्रश्न के लिए, यदि आप \( u=x^3 - 3xy^2 \) को देखेंगे, तो आपको यह साबित करने के लिए Laplace के समीकरण का उपयोग करना होगा। आपको \( \frac{\partial^2 u}{\partial x^2} + \frac{\partial^2 u}{\partial y^2} = 0 \) को सिद्ध करना होगा। सभी दूसरे समीकरणों के लिए इसे लागू करने से आपको यह पता करने में मदद मिलेगी कि क्या यह एक प्रंसवादी फलन है। अंत में, शक्ति श्रेणी के व्यास (radius of convergence) के लिए, आपको श्रेणी के सामान्य टर्म का प्रयोग करते हुए \( \limsup \) या \( \frac{1}{R} = \lim_{n \to \infty} |a_n|^{1/n} \) का उपयोग करना होगा। यहां से आप व्यास निर्धारित कर सकते हैं!

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad